Green Technology Acceptance Model and Green Logistics Operations: “To See Which Way the Wind Is Blowing” - Anser, Muhammad Khalid; Yousaf, Zahid; Zaman, Khalid (Frontiers in Sustainability, 2020)
This study provides a new insight to extend traditional technology acceptance model (TAM) in to energy –augmented TAM (EA-TAM) model in order to analyze micro-macro perspective of green enterprise technology to ensure eco-friendly products. The critical review would enhance analytical abilities to understand the main determinants of TAM model at both firms’ and industry perspective. The study proposed micro and macro enterprise energy –augmented TAM models and found that micro enterprise EA-TAM associated with green investment decision that increases the use of renewable energy demand to improve logistics performance, export capabilities, technology advancement, resource inputs and competitiveness. These factors would largely support to green product innovation, which is fueled by green R&D expenditures. The green supply chain process would develop an attitude and behavioral intention towards the use of technology and green products, which ultimately would bond with green system use. The macro perspective of EA-TAM shows that green factors including green supplier selection, industrial green engineering, green procurement, green consumerism, green product recovery, and green innovation would increase green purchase decisions that convert into perceived ease of green products usage. The eco-product choice faced three compelling issues that could negatively affect the use of green products attitude and intentions, i.e., political constraints, carbon pricing, and consumer willingness-to-pay for public goods. The study concludes that the need for green policies is imperative to regulate firms and the industrial decision to go-for eco-friendly production. The use of renewable energy, carbon pricing and willingness-to-pay for public goods would be recommended for long-term sustainable development.